Franz Boas and the Bella-Coolas in Berlin: human zoos, native performances and anthropological practice at the end of the 19th century - Vieira, Marina Cavalcante (Proa: Revista de Antropologia e Arte, 2024)
Nine Bella-Coola indigenous people from the northwest American coast toured Germany between 1885 and 1886. Promoted by Johan Adrian Jacobsen and Carl Hagenbeck, such human zoo shows used to raise great interest of the scientific societies of the time. Upon arriving in the capital Berlin, the Bella-Coola exhibition redirects Franz Boas' career and scientific interest, becoming a key event in his conversion to anthropology and further change to the United States. This article reconstitutes the Bella-Coola exhibition, and emphasizes the relationships established between Franz Boas and the troupe. As background unfolds a discussion about the importance of human zoos shows for the development of anthropology. Nueve indigenas Bella-Coola de la costa noroeste americana recorren Alemania entre 1885 y 1886. Patrocinados por Johan Adrian Jacobsen y Carl Hagenbeck, estos espectáculos zoológicos humanos despertaban gran interés entre las sociedades científicas de la época. Al llegar a la capital Berlín, la exposición Bella-Coola redirige la carrera y el interés científico de Franz Boas, convirtiéndose en un acontecimiento fundamental en su conversión a la antropología y su posterior traslado a los Estados Unidos. Este artículo reconstruye la exposición de Bella-Coola y destaca las relaciones establecidas entre Franz Boas y la troupe. De fondo, hay una discusión sobre la importancia de los espectáculos del zoológico humano para el desarrollo de la antropología practicada en la época. Nove indígenas Bella-Coola da costa noroeste americana saem em turnê pela Alemanha entre os anos de 1885 e 1886. Promovidos por Johan Adrian Jacobsen e Carl Hagenbeck, tais shows de zoológicos humanos costumavam levantar grande interesse das sociedades científicas da época. Ao chegar à capital, Berlim, a exibição Bella-Coola redireciona a carreira e o interesse científico de Franz Boas, tornando-se um evento basilar em sua conversão à antropologia e posterior mudança para os Estados Unidos. O presente artigo reconstitui a exibição ...